Nandalal Bose on Patrick and Arthur Geddes - Das, Shilpi (Summerhill IIAS Review, 2024)
Originally written in Bengali in 1922, the memoirs titled Patrick Geddes, 1922 and Arthur Geddes, authored by Nandalal Bose, were published in 1982. Here, Nandalal Bose, one of the pioneers of modern art in twentieth-century India, narrates his experience, interaction and engagement with both Patrick Geddes (1854-1932) and Arthur Geddes (1895-1968), and presents their views as the quintessence of Tagorean and Gandhian views. Within Patrick Geddes, Nandalal, widely renowned for reigniting the Indigenous painting style and popularizing pan-Asian art in the contemporary era, experienced his search for the vastness in the infinitesimal, global in the local as in Rabindranath Tagore and Mahatma Gandhi. Nandalal’s attempt to understand the Geddeses through the lenses of aesthetics of Tagore, and love for the ordinary of Mahatma Gandhi, make these memoirs highly interesting. In this essay, we get to know about how Patrick Geddes took the help of Rabindranath Tagore’s associates including Nandalal in making some significant alterations to the original plan of Tagore’s experimental university. The translated text thematically groups two short excerpts from the second volume of Bharatshilpi Nandalal, an edited memoir of the famous Bengali artist Nandalal Bose compiled by Panchanan Mandal. The first section is an account of Nandalal Bose’s interactions with Patrick Geddes, the Scottish town planner and sociologist who visited Santiniketan in 1922, followed by a shorter narrative of Patrick Geddes’ son Arthur Geddes’ visit next year. Because the text brings together three culturally significant early twentieth-century personalities, it can prove useful as a primary source for scholars and researchers working on Patrick Geddes, Jagdish Chandra Bose or Rabindranath Tagore. The text clarifies Patrick Geddes’ thoughts on Santiniketan as an experiment in pedagogy, architecture, and urban planning; offers Nandalal Bose’s perspective on art and aesthetics, his understanding of cultural differences between the East and the West, and his reflections on religious tolerance and coexistence as well as unthinking acceptance of caste dogmas at a crucial time in Indian history. This translation will interest a large number of scholars working on early twentieth-century Bengal or India or those simply curious about Bose, Geddes, and Tagore.